Poly(lactic acid) nanoparticles and cell-penetrating peptide potentiate mRNA-based vaccine expression in dendritic cells triggering their activation. (March 2019) - Coolen, Anne-Line; Lacroix, Céline; Mercier-Gouy, Perrine; Delaune, Emilie; Monge, Claire; Exposito, Jean-Yves; Verrier, Bernard
Abstract: Messenger RNA-based vaccines have the potential to trigger robust cytotoxic immune responses, which are essential for fighting cancer and infectious diseases like HIV. Dendritic Cells (DCs) are choice targets for mRNA-based vaccine strategies, as they link innate and adaptive immune responses and are major regulators of cytotoxic and humoral adaptive responses. However, efficient delivery of antigen-coding mRNAs into DC cytosol has been highly challenging. In this study, we developed an alternative to lipid-based mRNA delivery systems, using poly(lactic acid) nanoparticles (PLA-NPs) and cationic cell-penetrating peptides as mRNA condensing agent. The formulations are assembled in two steps: (1) formation of a polyplex between mRNAs and amphipathic cationic peptides (RALA, LAH4 or LAH4-L1), and (2) adsorption of polyplexes onto PLA-NPs. LAH4-L1/mRNA polyplexes and PLA-NP/LAH4-L1/mRNA nanocomplexes are taken up by DCs via phagocytosis and clathrin-dependent endocytosis, and induce strong protein expression in DCs in vitro . They modulate DC innate immune response by activating both endosome and cytosolic Pattern Recognition Receptors (PRRs), and induce markers of adaptive responses in primary human DCs in vitro, with prevalent Th1 signature. Thus, LAH4-L1/mRNA and PLA-NP/LAH4-L1/mRNA represent a promising platform for ex vivo treatment and mRNA vaccine development.